Tuber quality assessment of orange-fleshed sweet potato (Ipomoea batatas) cultivars and their genetic relatedness as revealed by SDS-PAGE of tuber proteins - ROY, S; BANERJEE, A; TARAFDAR, J; MITRA, S (The Indian Journal of Agricultural Sciences, 2012)
Orange-fleshed sweet potato (OFSP) is an important source of β-carotene and can make a major contribution in alleviating vitamin A malnutrition. Replacement of white-fleshed varieties with new b-carotene-rich OFSP cultivars that meet local preference would benefit the children who are at risk for vitamin A deficiency related problems. Twelve OFSP cultivars of diverse origin were analyzed for biochemical and antioxidant composition, viz dry matter, crude protein, crude fat crude fibre, carbohydrate, starch, amylose, reducing sugars, total phenols, ascorbic acid and b-carotene contents of their tubers. Many of the investigated cultivars have high levels of dry matter, crude protein, starch, β-carotene, phenols and ascorbic acid. Cultivars with high dry matter and b-carotene can be utilized to develop cultivars for commercial exploitation. This paper also highlights the genetic relatedness among the OFSP cultivars, assessed by using sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) of tuber proteins. High genetic similarities were observed among the cultivars originated in India.